Identity and addressivity in the "Beyond These Walls" program. (February 2017) - Liaw, Meei-Ling; English, Kathryn
Abstract: In a Taiwan-France telecollaborative project, Beyond These Walls, we designed a self-introduction activity to facilitate connective affordance between two groups of learners. Participants selected three objects – representing their past, present, and future – to their intercultural partners. Students prepared PowerPoint files and text documents to post on a project website. Participants then read, commented on, and asked/answered questions about the postings. To understand how the participants presented and positioned themselves during the processes of forming connectivity, the object descriptions and interactive postings were collected. Bakhtin's (1986; 1981) conceptions of audience and addressivity and the social presence theory of Gunawardena (1995) were used to analyze the data. Our findings suggest that objects reflected the participants' identities and personas, which helped to create a sense of physical presence that is frequently lacking in online communication. The acts of selecting, describing, reading, and discussing objects of personal significance were conducive to participants' awareness of one another's identities and shaped the perceptions of their interlocutors as authentic, identifiable individuals with whom interpersonal communication was possible. Based on these findings, we discuss the importance of identity and how identity construction strategies foster social presence that is essential in telecollaborative settings.